Friction material composites copper-/metal-free material design perspective - Sundarkrishnaa, K. L. (Springer International Publishing, 2015)
This book examines material composites used in connection with brake friction, their design and safety. To aid in understanding, the essentials of friction are explained. This second edition was extended to include friction material composites without copper, as they offer an environmentally friendlier option. The second edition is intended to support beginners by offering insights into the essentials of friction material composites, helping them to develop a broader understanding of brake friction materials. Friction materials find wide-ranging applications in household and industrial appliances, brake pads for automotive applications, rail brake friction pads and composition brake blocks. This second edition is an introductory volume to a set of related books, and is based on the author?s experience and expertise with various material manufacturers, brake manufacturers, vehicle manufacturers, researchers and testing labs around the world with which the author has been associated for the past 28 years.